Parental involvement and children’s cognitive and non-cognitive development: evidence from China - Wang, Hengli; Zhan, Ziyan; Zhang, Zuojunli (Frontiers in Psychology, 2026)
The development of children’s cognitive and non-cognitive abilities is a central concern in education and human capital research. Using nationally representative data from the China Education Panel Survey (CEPS), this study examines how parental involvement is associated with children’s cognitive and non-cognitive development in China. We focus on three dimensions of parental involvement—communication frequency, shared activities, and emotional closeness—and estimate their relationships with children’s cognitive skills and key non-cognitive traits, including emotional stability, conscientiousness, and agreeableness. The results show that higher levels of parental involvement are positively associated with both cognitive and non-cognitive outcomes. These associations remain robust across alternative specifications and quantile regressions. Further analyses reveal meaningful heterogeneity by gender, while differences by household registration status and boarding arrangements are less systematic. To explore the mechanisms underlying these relationships, the study conducts mediation analyses focusing on learning engagement and children’s confidence. The findings show that learning engagement serves as an important behavioral channel linking parental involvement to cognitive development, while both learning engagement and confidence play significant roles in shaping non-cognitive outcomes. Together, these results highlight that parental involvement influences children’s development through both behavioral and psychological pathways. Overall, the findings provide additional evidence on the role of parental involvement in children’s multidimensional development within China’s institutional and cultural setting and suggest that policies aimed at supporting parental engagement may contribute to improved child development outcomes.